PERANCANGAN SISTEM PENDATAAN SIDANG DAN ADMINISTRASI PRAKERIN SISWA SMK AL-MUHTADIN DEPOK - M. Aditya Hardiansyah; Yuli Haryanto; Abdul Mufti (Jurnal Ilmiah Hospitality, 2022)
The purpose of research is to build a system of data collection and prakerin administration application at SMK Al-Muhtadin Depok, to manage student prekerin data, trial tester data, and administrative payments. All processes are recorded manually so that often experience errors and difficulties when making student data reports prakerin or prekerin student payment reports, therefore a system is needed to process the student's administrative data. Data collection method conducted by grounded research method is a fact-based research method with the aim of establishing concepts, developing theory, collecting and analyzing data at the same time. The system is created using Java and MySQL databases. The data collection application system that has been created is used for the data collection of new prakerin students, the data collection of examiners, the prekerin trial and the data collection of prakerin administration